Optimization of a rhodamine 6G-doped PMMA thin-slab laser - Tou, T.Y.; Yap, S.S.; Chin, Oi Hoong; Ng, S.W. (2007)
Poly(methyl methacrylate) (PMMA) and Rhodamine 6G (Rh6G) were first dissolved in chloroform, then dried and milled into powdery preform for fabrication into rectangular thin slabs (< 1 mm) by a hot-press molding technique. Aluminum was coated on two surfaces of dye-doped PMMA thin slabs as reflectors. Conversion efficiency, peak lasing wavelength and spectral bandwidth of dye laser emissions from these slabs, which were transversely pumped by a nitrogen laser, were measured as a function of the dye concentration, slab thickness, and aluminum coatings. Re-absorption of back-scattered fluorescence due to aluminum coating on the opposite surface increased the conversion efficiency from 10.5 to 15 while that on the back surface further increased it to 17.5. The operation lifetime of 3000 pulses at 50 reduction in the dye laser output, as compared to earlier work on thicker slabs (5 mm), suggested that re-absorption of fluorescence did not cause significant photo-degradation of Rh6G. As the dye laser action was confirmed in a thin slab, the operation lifetime may represent a more realistic photostability of Rh6G in PMMA matrix. (c) 2006 Elsevier B.V. All rights reserved.